Gene transfer mediated by alpha2-macroglobulin. - Schneider, H (1996)
alpha2-Macroglobulin covalently linked to poly(L)-lysine can be used as a vehicle for receptor-mediated gene transfer. This modified alpha2-macroglobulin maintains its ability to bind to the alpha2-macroglobulin receptor, and was shown to introduce a luciferase reporter gene plasmid into HepG2 human hepatoma cells in vitro. The alpha2-macroglobulin receptor is a very large and multifunctional cell surface receptor, whose rapid and efficient internalization rate makes it attractive for gene therapy, e.g. for hepatic gene targeting via injection into the portal vein.